2021
DOI: 10.1136/bcr-2020-240496
|View full text |Cite
|
Sign up to set email alerts
|

A case of SARS-CoV-2 reinfection in a patient with obstructive sleep apnea managed with telemedicine

Abstract: The novel coronavirus (SARS-CoV-2) has produced millions of infections and deaths worldwide. It is believed that adaptive immunity to the virus occurs although with variation in its pattern and duration. While uncommon, confirmed reinfection with the novel coronavirus has been reported. Telemedicine has emerged as a viable tool for the delivery of healthcare in lieu of in-person patient contact. The variable and occasionally rapid course of clinical disease raises safety concerns of using telemedicine in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Likewise, 10 studies were identified via citation searching. These 10 were sought for retrieval and then assessed for eligibility [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 10 studies were identified via citation searching. These 10 were sought for retrieval and then assessed for eligibility [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ,…”
Section: Resultsmentioning
confidence: 99%
“…20,95 The wide variety of free software and platforms currently available, such as Zoom, WeChat, WhatsApp, Google Duo, WebEx, FaceTime, Redcap platform, Doxy.me platform, emails and also new software were introduced like e-CoVig, Microsoft Teams and TELEA tool; adequate lighting; good camera quality; and a good internet connection allow for the proper evaluation of patients. 40,41,44,48,53,54,57,71,[73][74][75]79,84 In current studies, Zoom was the most frequent application used mostly for Video-conference and virtual visits. 36,40,41,43,54,53,57,71,73,77,79,84 As telemedicine is being used widely, preparing specific guidelines by worldwide institutions (e.g., WHO) might help HCPs and patients feel safe when using telemedicine.…”
Section: Discussionmentioning
confidence: 90%
“…Also, this enables medical teams to cooperate and hold video meetings on complex and urgent situations. 64 , 73 , 75 , 76 , 84 Video conferencing was one of the most common technologies during the COVID-19 pandemic. Video conferencing is used in various situations, such as learning and videoconference and its role in teaching medical students and using this technology to maintain the education of residents, doctor-patient communication and communication between the medical team, Videoconference for clinical recommendations for treatment by the family of patients via providers during COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has emerged as a viable tool for the delivery of healthcare in lieu of in-person patient contact. The variable and occasionally rapid course of clinical disease raises safety concerns in using telemedicine in the clinical management of acute infection with the novel coronavirus [15]. In Australia, Hutchings et al, developed a virtual health care program or community management of patients with COVID-19 [16].…”
Section: Discussionmentioning
confidence: 99%